The Significance of Loyalty on Consumer Credit Profitability - Prihartono, Aditya Galih; Sumarwan, Ujang; Achsani, Noer Azam; Kirbrandoko, Kirbrandoko (Universitas Prasetiya Mulya, 2012)
The purpose of this research is to analyze and test the effect of customer loyalty on consumer credit profitability. Loyalty Index Score was developed to determine the level of customers’ loyalty level through 4 main variables; Longevity, Depth, Breadth and Referrals. The effect of Loyalty Index Score on profitability was further tested by path analysis to find out the significance direct relationship between loyalty and profitablity and the indirect relationship between the two variable through bucket. The result showed that loyalty has a significant effect on profitability either directly or indirectly. It was concluded that direct loyalty effect on profitability is lower than that of the indirect effect through bucket. The conclusion could be made by analyzing the available data from personal loan customers in one of the biggest multinational bank in indonesia during October 2010 until March 2011.